Formulation and Determination of Spf (Sun Protection Factor) Mulberry Leaf Extract Spray Gel Preparation (Morus Nigra L.) As Sunscreen in Vitro - Diah Kartika Putri; Mila Naura Shalsabila; Salsabila Salsabila; Riska Nur Aeni; Rena Tiyarma Sari; Afina Rizky Ramadhani; Annajim Daskar; Wina Safutri; Vicko Suswidiantoro; Debby Heldayani (Majalah Kesehatan Indonesia, 2026)
Excessive exposure to ultraviolet (UV) radiation is associated with a wide range of adverse skin effects, including erythema, photoageing, and an increased risk of skin cancer, highlighting the need for effective photoprotective formulations. This study aimed to formulate a spray gel containing mulberry leaf (Morus nigra L.) extract and to evaluate its in vitro Sun Protection Factor (SPF) alongside its physicochemical characteristics. Mulberry leaf extract was incorporated into spray gel formulations at concentrations of 0.75% (F1), 3.75% (F2), and 6.75% (F3). All formulations were prepared in triplicate and evaluated for organoleptic properties, homogeneity, pH, viscosity, spray pattern, and in vitro SPF using the UV–Visible spectrophotometric method based on the Mansur equation. Statistical analysis was performed using the Shapiro–Wilk and Levene tests followed by appropriate non-parametric analysis when assumptions of normality and homogeneity were not satisfied (p < 0.05). The mean SPF values obtained were 25.09 (Ultra), 25.74 (Ultra), and 36.98 (Ultra) for F1, F2, and F3, respectively, demonstrating a concentration-dependent increase in photoprotective activity. All formulations exhibited acceptable physicochemical characteristics for spray gel preparations throughout the evaluation period. Among the tested formulations, F3 (6.75%) produced the highest in vitro SPF value. These findings indicate that Morus nigra leaf extract possesses promising in vitro photoprotective potential for spray gel formulations. However, further stability, photostability, skin compatibility, and in vivo studies are required before practical application can be recommended